Utilization of Electronic Records in Management Decision Making at Uganda College of Commerce-Kabale. - Agaba, Gideon (Kabale University, 2023)
The study investigated utilization of electronic records in management decision making at Uganda College of Commerce -Kabale. The objectives of the study were; to establish the types of electronic records utilized and managed by Uganda College of Commerce Kabale, to identify the challenges encountered in management of electronic records for decision making at Uganda College of Commerce-Kabale and to suggest possible solutions to the challenges encountered in management of electronic records for decision making at Uganda College of Commerce-Kabale. A descriptive research design was used and data was collected using interviews. The study findings on types of electronic records utilized and managed by Uganda College of Commerce -Kabale were; transcripts, admissions letters, payment slips, employment records and financial records. There are many challenges encountered in management of electronic records for decision making at Uganda College of Commerce-Kabale which included in adequate communication infrastructure, inadequate technical knowledge among the employees, inadequate finance to facilitate electronic records management and improper planning of information resources. The possible solutions to the challenges encountered in management of electronic records for decision making at Uganda College of Commerce-Kabale were; training of records management staff, financing electronic records management, having a records management policy and ensuring better planning of information resources. The study recommended that there should be user education on utilization of electronic records so as to enable the concerned staff make proper use of them for better decision making and there should be government intervention by providing enough funds to help in purchasing of enough instruments to use in accessing electronic records like enough computers at Uganda College of Commerce -Kabale.